Bovine tropical theileriosisÂ· A potpourri - GILL, B S (The Indian Journal of Animal Sciences, 2013)
With a view to increasing milk production in short time, extensive programmes of improving indigenous cattle by breeding them With exotic dairy cattle are under way in many a Third world countries including India. The success of these programmes is threatened by theileriosis (Theileria annulala) as the improved cattle arc highly susceptible to the disease after suffering mertality of up to 90%. 'The infection scenario in nature being subject to several variables need critical evaluation for arriving at correct diagnosis. The author has described here 7 natural outbreaks of theileriosis, their course, signs and results of laboratory examination and discussed critically the dala establishing definitive diagnosis.